The Putative Role of mTOR Inhibitors in Non-tuberous Sclerosis Complex-Related Epilepsy - Goldstein, Hannah E.; Hauptman, Jason S. (Frontiers in Neurology, 2021)
Epilepsy affects approximately 5 out of every 10,000 children per year. Up to one-third of these children have medically refractory epilepsy, with limited to no options for improved seizure control. mTOR, a ubiquitous 289kDa serine/threonine kinase in the phosphatidylinositol 3-kinase (PI3K)-related kinases (PIKK) family, is dysregulated in a number of human diseases, including tuberous sclerosis complex (TSC) and epilepsy. In cell models of epilepsy and TSC, rapamycin, an mTOR inhibitor, has been shown to decrease seizure frequency and duration, and positively affect cell growth and morphology. Rapamycin has also been shown to prevent or improve epilepsy and prolong survival in animal models of TSC. To date, clinical studies looking at the effects of mTOR inhibitors on the reduction of seizures have mainly focused on patients with TSC. Everolimus (Novartis Pharmaceuticals), a chemically modified rapamycin derivative, has been shown to reduce seizure frequency with reasonable safety and tolerability. Mutations in mTOR or the mTOR pathway have been found in hemimegalencephaly (HME) and focal cortical dysplasias (FCDs), both of which are highly correlated with medically refractory epilepsy. Given the evidence to date, a logical next step is to investigate the role of mTOR inhibitors in the treatment of children with medically refractory non-TSC epilepsy, particularly those children who have also failed resective surgery.